A comparison of developmental reasons for substance use between sexual minority and heterosexual emerging adults. Issue 3 (3rd July 2022) - Clary, Kelly Lynn; Goffnett, Jacob; Bennett, Kyle; Smith, Douglas
Abstract: Emerging adults (EAs; 18–29 years) have the highest rates of substance use across the lifespan, with some research displaying sexual minority EAs are at higher risk of substance use than their heterosexual counterparts. We explored differences in rates of substance use and developmental reasons for alcohol, binge drinking, and cannabis between sexual minority and heterosexual EAs. Participants ( n = 145) in a randomized control trial completed Emerging Adult Reasons for Substance Use (EARS) and substance use frequency measures, pertaining to the past 90 days. Although unsolicited, 17% ( n = 25) of the sample identified as a sexual minority (i.e., not exclusively heterosexual). EARS concepts include developmental strain, subjective invulnerability, and normative expectancy. Sexual minority EAs experienced greater developmental strain, putting them at risk for problematic substance use. Compared to their heterosexual peers, sexual minority EAs reported higher alcohol and cannabis use, significantly higher binge-drinking, and were identified as hazardous drinkers by the Alcohol Use Disorders Identification Tool (AUDIT-C). Future research should continue to examine dimensions of emerging adulthood and substance use with larger samples of sexual minority EAs and with qualitative methods. Practitioners should address unique developmental stressors sexual minority EAs experience when assisting those with substance use problems.